Percutaneous transbiliary biopsy - ANDRADE,GUSTAVO VIEIRA (2017)
ABSTRACT Percutaneous drainage of the bile ducts is an established procedure for malignant obstructions, in which a histological diagnosis is often not obtained. We describe the biopsy technique of obstructive lesions through biliary drainage access, using a 7F endoscopic biopsy forceps, widely available; some are even reusable. This technique applies to lesions of the hepatic ducts, of the common hepatic duct and of all extension of the common bile duct.